Best Proximity Point Theorems for Cyclic Wardowski Type Contraction: Lakshmi Kanta Dey, Saranan Mondal - Team, Support (Thai Journal of Mathematics, 2020)
In this article, we give an extended version of fixed point result for Wardowski type contraction and define a new type of contraction namely, cyclic Wardowski type contraction or cyclic F-contraction in a complete metric space. Moreover, we prove the existence of best proximity point for cyclic F-contraction and also establish best proximity result in the setting of uniformly convex Banach space.